Linear parks of Tremembé: the use of green infrastructure to create a system of free spaces - Lima, Gerson Amaral; Pellegrino, Paulo Renato Mesquita (Paisagem e Ambiente, 2015)
This work consists in developing a proposal for a landscape intervention in the area of the Subprefeitura Tremembé/Jaçanã, in São Paulo. The region constitutes the buffer zone of the Cantareira State Park and the densification of the neighborhood threatens the preservation of the local environment. The project takes as its guideline the treatment of urban waters, especially in requalification of river valleys, introducing new concepts of urban water management that are based on the idea of Low Impact Development (LID). The proposal also seeks to set up a new relation between the city and its natural resources, weaving a new relation between the forest and the city.